2019
DOI: 10.1136/bmjsrh-2019-200487
|View full text |Cite
|
Sign up to set email alerts
|

Primary care providers’ knowledge, attitudes and practices of medical abortion: a systematic review

Abstract: BackgroundDespite the availability of medical abortifacients, and their potential use in primary care, only a small proportion of primary healthcare professionals provide medical abortion services. Understanding the perspectives of primary care providers on delivering medical abortion is pertinent to identifying barriers to medical abortion service provision and increasing access for women globally.ObjectiveTo understand the knowledge, attitudes and practices of primary healthcare providers regarding medical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…Although the Therapeutic Goods Administration (TGA) approved mifepristone for use as a medical abortifacient during early pregnancy in 2012 1 and MS‐2 Step (composite regimen of mifepristone and misoprostol) has been subsidised by the Pharmaceutical Benefits Scheme since 2015, 1 integration of early medical abortion into primary health care has been slow 4 . In December 2020, only 2841 of 29 017 registered GPs were active prescribers of MS‐2 Step, and 5347 of 32 393 registered pharmacists were active dispensers 5…”
mentioning
confidence: 99%
“…Although the Therapeutic Goods Administration (TGA) approved mifepristone for use as a medical abortifacient during early pregnancy in 2012 1 and MS‐2 Step (composite regimen of mifepristone and misoprostol) has been subsidised by the Pharmaceutical Benefits Scheme since 2015, 1 integration of early medical abortion into primary health care has been slow 4 . In December 2020, only 2841 of 29 017 registered GPs were active prescribers of MS‐2 Step, and 5347 of 32 393 registered pharmacists were active dispensers 5…”
mentioning
confidence: 99%
“…A study conducted in 23 medical students in India revealed that the lack of knowledge regarding the procedure and the current law of the country contributed to their disapproval of pregnancy terminations [29]. Moreover, appropriate knowledge will support primary care providers and nurses in delivering medical abortion services and increasing access for women [30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on pharmacists' knowledge of mifepristone dispensing have been conducted in countries with regulations that are different from those in the United States, where pharmacists are often the first point of care. [18][19][20] Pharmacists' perspectives on dispensing mifepristone for medication abortion are largely missing from the literature, even internationally. 19,21,22 The purpose of this analysis was to assess the feasibility of the model by measuring the differences in pharmacists' knowledge about medication abortion and their perspectives on mifepristone dispensing before and after the intervention, as well as the proportion of pharmacists who refused to dispense mifepristone to patients.…”
Section: Objectivesmentioning
confidence: 99%